The Relationship Between Personal Hygiene and The Incidence of Tyhpoid Fever in The Working Area of The Health Center - Chatherine, Augnesia Seven; Siagian , Hotmaida; Suprihatin, Kusmini; Yusop, Nooreena (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2025)
Typhoid fever or abdominal typhoid is an infectious disease that usually affects the digestive tract with symptoms of fever for more than 7 days. This disease is caused by Salmonella typhi. Transmission occurs through a person's personal hygiene. This research is a descriptive research with a survey method with a random sampling technique, which is a sampling technique by selecting a sample from among the population. This research was conducted in February-March 2023. Using questionnaires and medical records. The results of the study on poor personal hygiene were 28 people (56%) in the category of severe fever, respondents with sufficient personal hygiene and good personal hygiene did not have severe fever. Results Analysis using the chi-square statistical test showed results (P Value = 0.000 <0.05) so that there was a significant relationship between personal hygiene and the incidence of typhoid fever. The majority of a person has a severe fever, this can occur due to poor personal hygiene. The majority of people have poor personal hygiene, this is due to a lack of knowledge about personal hygiene with the incidence of typhoid fever. There is a relationship between personal hygiene and the incidence of typhoid fever at the Candi Health Center, this is because families pay less attention to personal hygiene, such as the habit of not washing hands before and after eating, not washing hands after going to the toilet, and eating snacks outside the home.